(untitled) (Texas Journal of Medical Science, 2024)
31 children with initial manifestations of spinal deformity were studied of varying degrees and severity of scoliotic disease. It has been established that the first clinical signs of spinal deformities appear at the age of no more than 10 years. those. before the beginning of the period of physiological maturation of the body. Analysis of the obtained data makes it possible to determine the proportions of various variants of the natural development of scoliotic spinal deformity. This makes it possible to predict the prospects for the development of pathology in patients with scoliosis.